2020
DOI: 10.1177/2516103220940325
|View full text |Cite
|
Sign up to set email alerts
|

Indiscriminate friendliness in foster children: Associations with attachment security, foster parents’ sensitivity, and child inhibitory control

Abstract: Indiscriminate friendliness (IF) is atypical behavior often seen in postinstitutionalized and foster children. The current exploratory study examined the associations of children’s attachment security, parental sensitivity, and child inhibitory control with reported and observed IF in 60 family-reared, never-institutionalized foster children. IF was measured with a parent-report questionnaire (Indiscriminate Friendliness Questionnaire) and an observational measure (adapted version of the Stranger at t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 46 publications
0
4
0
1
Order By: Relevance
“…Another randomised study with adoptive families took place in Italy and was reported in two publication (Barone et al, 2019; Barone, Barone, et al, 2018). Finally VIPP was used in a randomised study in Holland using foster families, and this study was reported in Schoemaker et al (2020).…”
Section: Resultsmentioning
confidence: 99%
“…Another randomised study with adoptive families took place in Italy and was reported in two publication (Barone et al, 2019; Barone, Barone, et al, 2018). Finally VIPP was used in a randomised study in Holland using foster families, and this study was reported in Schoemaker et al (2020).…”
Section: Resultsmentioning
confidence: 99%
“…In fact, Dylan developed DSED after RAD resolved, and its appearance seemed associated with that shift. According to his verbalisation that 'More is always better', he may have generalised his trusting relationship with his foster carers to other adult relationships (Schoemaker et al, 2020;Vervoort et al, 2014), perhaps to ensure continued care in the event of further placement disruptions (Gorter et al, 2017;Minnis et al, 2006). Not only did he exhibit DSED along with improved use of his carers for support, nurture and soothing, he may also have developed this condition precisely because he enjoyed feeling safe and nurtured.…”
Section: Discussionmentioning
confidence: 99%
“…While researchers agree that RAD and DSED capture important relational phenomena not accounted for in other diagnoses (Gleason et al., 2011), many questions remain about the mechanisms underlying their development. The neurobiological effects of stress, genetics and working models of attachment have all been posited as potential mediators (Dahmen et al., 2012; Rutter et al, 2010; Schoemaker et al, 2020).…”
Section: Understanding the Development Of Rad And Dsedmentioning
confidence: 99%
See 1 more Smart Citation
“…A Rorschach-teszt eredményei alapján feltűnő a kötődési probléma jelenléte. Számos kutatás (Schoemaker et al, 2020;Lehmann et al, 2020;O'Connor, Woolgar, Humayun, Briskman & Scott, 2019) mutatott ki diszinhibíciós (gátolatlan) kötődési zavart intézetben nevelkedett serdülőknél. Ezekre a gyermekekre általánosan jellemző, hogy könnyen mennek el idegenekkel, és az általuk nem ismert személyekkel válogatás nélkül kedvesek, ragaszkodók.…”
Section: Rorschach-próbaunclassified